A synoptic climatology of heavy rain events in the Lake Eyre and Lake Frome catchments - Pook, Michael J.; Risbey, James S.; Ummenhofer, Caroline C.; Briggs, Peter R.; Cohen, Timothy J. (Frontiers in Environmental Science, 2014)
The rare occasions when Lake Eyre in central, southern Australia fills with water excite great interest and produce major ecological responses. The filling of other smaller lakes such as Lake Frome, have less impact but can contribute important information about the current and past climates of these arid regions. Here, the dominant synoptic systems responsible for heavy rainfall over the catchments of Lake Eyre and Lake Frome since 1950 are identified and compared. Heavy rain events are defined as those where the mean catchment rainfall for 24 hours reaches a prescribed threshold. There were 25 such daily events at Lake Eyre and 28 in the Lake Frome catchment. The combination of a monsoon trough at mean sea level and a geopotential trough in the mid-troposphere was found to be the synoptic system responsible for the majority of the heavy rain events affecting Lake Eyre and one in five of the events at Lake Frome. Complex fronts where subtropical interactions occurred with Southern Ocean fronts also contributed over 20% of the heavy rainfall events in the Frome catchment. Surface troughs without upper air support were found to be associated with 10% or fewer of events in each catchment, indicating that mean sea level pressure analyses alone do not adequately capture the complexity of the heavy rainfall events. At least 80% of the heavy rain events across both catchments occurred when the Southern Oscillation Index (SOI) was in its positive phase, and for Lake Frome, the SOI exceeded +10 on 60% of occasions, suggesting that the background atmospheric state in the Pacific Ocean was tilted towards La Niña. Hydrological modeling of the catchments suggests that the 12-month running mean of the soil moisture in a sub-surface layer provides a low frequency filter of the precipitation and matches measured lake levels relatively well.